Preparing for a national weightlifting championship: A case study - Travis, K.; Mizuguchi, S.; Stone, M. H.; Sands, W. A.; Bazyle, C. D. (2018 NSCA National Conference at: Indianapolis, Indiana, USA, 2018)
INTRODUCTION: Monitoring an athlete`s psychological, physiological, and performance level is important when preparing for a major competition (COMP). No study to date has tracked a high-level weightlifter peaking for a major COMP all the way up to the day of COMP. Assessing performance at a COMP is vital to ascertain if the athlete has reached a peak and if peak performance will actually be expressed during the COMP. PURPOSE: Therefore, the purpose of this study was to determine when peak jumping performance was achieved and whether psychological or physiological variables explained any jump performance changes in a high-level female weightlifter preparing for a national COMP. We hypothesized that jumping performance would peak on COMP day corresponding with improved recovery and stress states and preserved muscle cross-sectional area (CSA) relative to baseline values. METHODS: A USA national-level female weightlifter (23.5y;54.0±0.6kg;155.4cm) competing in the 53kg weight class participated in this investigation. Laboratory testing was carried out over a 7-month period as part of an ongoing long-term athlete monitoring program. At 11-weeks out, testing was administered twice a week for each week leading up to COMP, at the COMP, and returning from the COMP. Each testing session evaluated body mass, recovery-stress inventories using the short recovery stress scale (SRSS), and vastus lateralis CSA via ultrasonography followed by a standardized warm-up preceding unloaded squat jumps (SJ) performed on dual force plates sampling at 1kHz. Hopkin`s effects size (ES) classifications for each data point was used to determine the potential magnitude of change observed for each test relative to baseline values. The smallest worthwhile change was used to determine a meaningful change relative to baseline values. The typical error and smallest worthwhile change were used to quantify the probability (i.e., precision, likelihood) that a performance change took place. Values greater or less than baseline values with precision >95% signified a very likely change for each testing session relative to the COMP. RESULTS: Weightlifting performance goals were met for the national championship (snatch=67kg, clean and jerk=92kg, total=159kg). Jumping performance (precision=99%; ES=2.7) was almost certainly peaked on COMP day with increased recovery (ES=0.7) and decreased stress scores (ES=0.5). However, the athlete possibly exhibited a small decrease in muscle CSA (precision=64.8%, ES=0.4) the week of COMP that corresponded with very large decreases in body mass (precision=99%; ES=2.8). CONCLUSIONS: The training program was effective in ensuring the athlete was peaked the day of COMP based on jumping performance and recovery-stress scores despite possibly small decreases in CSA. Thus, weightlifting coaches and sport scientists working with high-level weightlifters should monitor jumping performance and recovery-stress states to ensure athletes peak at an appropriate time. PRACTICAL APPLICATIONS: Sport scientists and coaches implementing a 1-week overreach and 3-week exponential taper might expect high-level weightlifters to achieve and maintain peak performance 3-4 days prior to COMP.